2015
DOI: 10.1016/j.genhosppsych.2015.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators of suicide risk assessment in emergency departments: a qualitative study of provider perspectives

Abstract: Objective: To understand emergency department (ED) providers' perspectives regarding the barriers and facilitators of suicide risk assessment and to use these perspectives to inform recommendations for best practices in ED suicide risk assessment. Methods: Ninety-two ED providers from two hospital systems in a Midwestern state responded to open-ended questions via an online survey that assessed their perspectives on the barriers and facilitators to assess suicide risk as well as their preferred assessment meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 32 publications
0
55
0
13
Order By: Relevance
“…[26] In our study, patients seen only by an ED physician, without an evaluation by a mental health consultant, were less likely to have documented lethal means assessment. This may relate to differences in training or awareness about lethal means counseling among ED and mental health providers, but it may also stem from overall perceived level of risk.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…[26] In our study, patients seen only by an ED physician, without an evaluation by a mental health consultant, were less likely to have documented lethal means assessment. This may relate to differences in training or awareness about lethal means counseling among ED and mental health providers, but it may also stem from overall perceived level of risk.…”
Section: Discussionmentioning
confidence: 87%
“…The suboptimal rates of lethal means assessment may stem from issues related to providers (e.g., inadequate training or unclear delineation of responsibilities) [13,14,[23][24][25] and the ED environment (e.g., busy and crowded). [26] In our study, patients seen Dotted areas represent patient populations of higher concern (discharged home; without documented assessment of access to lethal means; and with ࣙ1 firearm at home).…”
Section: Table 2 Medical Record Characteristics Of Participants By mentioning
confidence: 99%
“…The literature indicates that health professionals, including emergency nurses, predominantly report experiencing less positive feelings (Yaseen et al., ) and more negative attitudes towards patients with suicidal behaviour (Carmona‐Navarro & Pichardo‐martínez, ; Hawton, Casañas I Comabella, Haw, & Saunders, ); these attitudes are further compounded by resistance from health professionals to attend to mental health patients (Bertolote, De Mello‐Santos, & Botega, ). Additionally, studies have shown that emergency department nurses may have moralistic attitudes towards suicide, may blame the suicidal patient (Petrik, Gutierrez, Berlin, & Saunders, ), may be less likely to understand and be sympathetic and may be less likely to verbally interact with suicidal patients (Kishi, Kurosawa, Morimura, Hatta, & Thurber, ).…”
Section: Introductionmentioning
confidence: 99%
“…[13, 14] Studies have also demonstrated past experiences with providers[15], privacy concerns, interactions with other patients, and patient participation during assessment as influences to healthcare utilization in the depressed population. [16] Qualitative data has also revealed several recurring themes with regard to difficulties accessing care. From the perspective of PCPs, concerns over competence were common, such that roughly 41% did not feel confident in providing depression care.…”
Section: Introductionmentioning
confidence: 99%